Cis-mediated interactions of the SARS-CoV-2 frameshift RNA alter its conformations and affect function. Issue 2 (20th December 2022) - Pekarek, Lukas; Zimmer, Matthias M; Gribling-Burrer, Anne-Sophie; Buck, Stefan; Smyth, Redmond; Caliskan, Neva
Abstract: The RNA genome of SARS-CoV-2 contains a frameshift stimulatory element (FSE) that allows access to an alternative reading frame through −1 programmed ribosomal frameshifting (PRF). −1PRF in the 1a/1b gene is essential for efficient viral replication and transcription of the viral genome. −1PRF efficiency relies on the presence of conserved RNA elements within the FSE. One of these elements is a three-stemmed pseudoknot, although alternative folds of the frameshift site might have functional roles as well. Here, by complementing ensemble and single-molecule structural analysis of SARS-CoV-2 frameshift RNA variants with functional data, we reveal a conformational interplay of the 5′ and 3′ immediate regions with the FSE and show that the extended FSE exists in multiple conformations. Furthermore, limiting the base pairing of the FSE with neighboring nucleotides can favor or impair the formation of the alternative folds, including the pseudoknot. Our results demonstrate that co-existing RNA structures can function together to fine-tune SARS-CoV-2 gene expression, which will aid efforts to design specific inhibitors of viral frameshifting.